Determinan Yang Mempengaruhi Terjadinya Bendungan Asi pada Ibu Postpartum di Kabupaten Bulukumba - Husnul Khatimah; Sumarni Sumarni; Sitti Nurul Hikma Saleh; Kurniati Akhfar (Universitas Katolik Widya Karya Malang, 2023)
In Indonesia, there were 35,985 postpartum mothers who experienced ASI dams or (15.60%) postpartum mothers, and in 2015 postpartum mothers who experienced ASI dams were 77,231 or (37.12%). The increasing incidence of ASI dams is one of the health problems in Indonesia. Where this greatly affects the postpartum period, namely the failure to provide breast milk to infants and one of the failures to achieve coverage of exclusive breastfeeding. This study aims to determine the determinants that influence the occurrence of breast milk dams in postpartum mothers in Bulukumba Regency. This research is a quantitative descriptive study with a population of 30 postpartum mothers using total sampling. The results showed that the nipple length was the most influential factor among the five factors causing breast milk dams in the working area of ​​the Ujung Loe Health Center, Bulukumba Regency. This is based on a simple linear regression test obtained a p value of 0.04. Conclusion: From the results of the research conducted, it is known that all respondents who experienced breast milk retention were 19 mothers and 11 mothers who did not experience breast milk retention. After statistical tests were carried out using a simple linear regression test, it was found that there was a significant relationship between the causal factors, namely the nipples being too long and the occurrence of breast milk dams with a p value of 0.001.